Effect of Temperature on The Solvent Extraction of Cobalt(II), Nickel(II), and Copper(II) Metal Ions by o-diphenylamino Benzoic Acid - Matheel D. Al-Sabti (Engineering and Technology Journal, 2008)
The solvent extraction of cobalt, nickel, and copper ions by the ligand odiphenylaminobenzoic acid in chloroform at 273, 293, and 318 K has beeninvestigated. The values of pH1/2 and kex as well as the values for the thermodynamicparameters ΔG, ΔH, and ΔS have been calculated.